Physicochemical Properties, In vitro Starch Digestibility and Estimated Glycemic Index Following the Accelerated Aging of Freshly Harvested Rice - Millati, Tanwirul; Pranoto, Yudi; Utami, Tyas; Bintoro, Nursigit (Pakistan Journal of Nutrition, 2019)
Background and Objective: Cooked freshly harvested rice has high starch digestibility and a high glycemic index. This study aimed to examine the effect of the temperature and duration of accelerated aging on the physicochemical properties of freshly harvested rice, including in vitro starch digestibility and the estimated glycemic index of cooked rice. Materials and Methods: The rice used was freshly harvested IR 64 variety with 27.36±0.73% moisture content. The accelerated aging process was conducted at various temperatures and durations, namely, room temperature (24-30°C), 40, 50, or 60°C and 2, 4 or 6 days. The parameters quantified were free fatty acid levels, amylose content, thermal and pasting properties, starch digestibility and estimated glycemic index of cooked rice. Results: Free fatty acids, amylose-lipid complexes and thermal properties increase during accelerated aging treatment. The pasting properties increased at 40°C, while at 60°C, there was a slight decrease in all properties except for the pasting temperature, which increased. The starch digestibility and estimated glycemic index decreased and the lowest values were obtained from accelerated aging at 40°C for 4 days, which was not significantly different from 60°C for 4 days, with estimated glycemic index values of 68.61 and 69.82, respectively. Conclusion: The accelerated aging of freshly harvested rice reduced starch digestibility and the estimated glycemic index of cooked rice. The best temperature and time for reducing the starch digestibility and changing the estimated glycemic index of cooked rice from the high to medium category were 40°C and 4 days.